Stability Study of Morphine and Baclofen Solution in Polypropylene Syringes - Robert Julien; Sorrieul Jérémy; Kieffer Hélène; Folliard Caroline; Gibory Vincent; Dupoiron Denis; Devys Catherine (De Gruyter, 2017)
The association of morphine and baclofen is used for the treatment of spasticity related pain. Moving these patients is sometimes difficult. In order to transport these syringes for pump refilling, it could be interesting to demonstrate the stability of the mixture, and so to be able to ensure the best transport conditions of syringes.